O sentido do espaço na iconografia do aldeamento missionário de São Fidélis - Barros, Clara Emília Sanches Monteiro de (1992)
The establishmen of order and rules, determined for the Indian,the role that he should play in the settlement, seducing him though severel ways of power exercise, that reproduced the ideological machine of the Church. The missionaries would show this way, their strength to manipulate the settlement functionality itself. Indirectly, the power was taken through several means including the practices of the missionaries, who proceeded to the appropriation and change for new purposes of the indian cultural inheritance built with the mithology from which, the necessaries allegories were elaborated, and still the theater, the processions and the sermons were done as part of the missionary pedagogy. It was at the functionality of this space that we found the meaning of theatrelization brought from the iconographic analysis.